Three blind mice; de collecties : Visser, Peeters, Becht; Stedelijk van Abbemuseum, Eindhoven, 6 april - 19 mei 1968. (Eindhoven : Stedelijk Van Abbemuseum, 1968)
van Amen, Woody ; Andre, Carl ; Arakawa, Shusaku ; Arman ; Arroyo, Eduardo ; Beuys, Joseph ; Blake, Peter ; Bontecou, Lee ; Broodthaers, Marcel ; Brusse, Mark ; Burgering, Toni ; Castro, Lourdes ; Christo ; Conner, Bruce ; Darboven, Hanne ; Dietman, Erik ; Dine, Jim ; Englund, Lars ; Riverhead (New York) ; Fontana, Lucio ; Frenken, Jaak ; Gilardi, Piero ; van Golden, Daan ; De Haan, Jurjen ; Hendrikse, Jan ; Van Hoeydonck, Paul ; Indiana, Robert ; Jacquet, Alain ; Johns, Jasper ; Judd, Donald ; Kelly, Ellsworth ; Kienholz, Edward ; Krushenick, Nicholas ; Kudo, Tetsumi ; Kusama Yayoi ; Lacey, Bruce ; LeWitt, Sol ; Lichtenstein, Roy ; Manzoni, Piero ; Morris, Robert ; Oldenburg, Claes ; Panamarenko ; Poons, Larry ; Rauschenberg, Robert ; Raynaud, Jean Pierre ; Raysse, Martial ; Rosenquist, James ; Rotella, Mimmo ; Sanejouand, Jean-Michel ; Schippers, Wim T. ; Schoonhoven, Jan ; Segal, George ; Spoerri, Daniel ; Stella, Frank ; Struycken, Peter ; Takis ; Uecker, Günther ; Visser, Carel ; Warhol, Andy ; Wesselman, Tom ; Westerik, Co
kunstcatalogus